Development of "Intention to Use Oral Contraception" Questionnaire based on Theory of Planned Behavior in women Using Withdrawal Method - Parvin Rahnama; Alireza Hidarnia; Ali Montazeri; Farkhondeh Amin Shokravi; Anoushiravan Kazemnejad (Tehran University of Medical Sciences, 2013)
Background & Aim: Need assessment for promotion reproductive health is important subject and development a questionnaire is essential. Thus the aim of this study was development of questionnaire of intention to use of oral contraception in withdrawal users based on construct of Theory of Planned Behavior (TPB).   Methods & Materials : In-depth interviews were conducted to elicit the salient beliefs relevant to oral contraception among withdrawal users. Then a cross-sectional study carried out in Tehran, Iran for validate of questionnaire. Participants recruited from attending five family planning clinics of public health services in the Eastern district of Tehran, Iran. Validity and reliability was evaluated using concurrent, content validity and Cronbachchr('39')s alpha and test- retest respectively. Factor structure of the questionnaire was extracted by exploratory factor analysis (EFA). Confirmatory factor analysis (CFA) conducted to assess how well the EFA extracted model fits observed data. The SPSS version 16 and Lisrel programs were used to analyze the data.   Results: Reliability and validity were confirmed. The principal component analysis revealed a three-factor structure for the questionnaire including attitude, subjective norm and perceive behavior control that explained 50.4 percent of the total of variance.   Conclusion : In general, the findings suggest that questionnaire of intention to use of oral contraception in withdrawal users based on Theory of Planned Behavior is a reliable and valid measure.